Guidelines for the diagnosis and management of gastroesophageal reflux disease: an evidence-based consensus - Moraes-Filho,Joaquim Prado P. (2010)
Gastroesophageal reflux disease (GERD) is one of the most common disorders in medical practice. A number of guidelines and recommendations for the diagnosis and management of GERD have been published in different countries, but a Brazilian accepted directive by the standards of evidence-based medicine is still lacking. As such, the aim of the Brazilian GERD Consensus Group was to develop guidelines for the diagnosis and management of GERD, strictly using evidence-based medicine methodology that could be clinically used by primary care physicians and specialists and would encompass the needs of physicians, investigators, insurance and regulatory bodies. A total of 30 questions were proposed. Systematic literature reviews, which defined inclusion and/or exclusion criteria, were conducted to identify and grade the available evidence to support each statement. A total of 11,069 papers on GERD were selected, of which 6,474 addressed the diagnosis and 4,595, therapeutics. Regarding diagnosis, 51 met the requirements for the analysis of evidence-based medicine: 19 of them were classified as grade A and 32 as grade B. As for therapeutics, 158 met the evidence-based medicine criteria; 89 were classified as grade A and 69 as grade B. In the topic Diagnosis, answers supported by publications grade A and B were accepted. In the topic Treatment only publications grade A were accepted: answers supported by publications grade B were submitted to the voting by the Consensus Group. The present publication presents the most representative studies that responded to the proposed questions, followed by pertinent comments. Follow examples. In patients with atypical manifestations, the conventional esophageal pH-metry contributes little to the diagnosis of GERD. The sensitivity, however, increases with the use of double-channel pH-metry. In patients with atypical manifestations, the impedance-pHmetry substantially contributes to the diagnosis of GERD. The examination, however, is costly and scarcely available in our country. The evaluation of the histological signs of esophagitis increases the diagnostic probability of GERD; hence, the observation of the dimensions of the intercellular space of the esophageal mucosa increases the probability of diagnostic certainty and also allows the analysis of the therapeutic response. There is no difference in the clinical response to the treatment with PPI in two separate daily doses when compared to a single daily dose. In the long term (>1 year), the eradication of H. pylori in patients with GERD does not decrease the presence of symptoms or the high recurrence rates of the disease, although it decreases the histological signs of gastric inflammation. It seems very likely that there is no association between the eradication of the H. pylori and the manifestations of GERD. The presence of a hiatal hernia requires larger doses of proton-pump inhibitor for the clinical treatment. The presence of permanent migration from the esophagogastric junction and the hernia dimensions (>2 cm) are factors of worse prognosis in GERD. In this case, hiatal hernias associated to GERD, especially the fixed ones and larger than 2 cm, must be considered for surgical treatment. The outcomes of the laparoscopic fundoplication are adequate.